SARCOF-31: Turning climate forecasts into actionable advisories - Gamoyo, Majambo; Ahmed, Jemal Seid; Ghosh, Aniruddha (2025)
This report presents outcomes of the Alliance of Bioversity International and CIAT’s technical and institutional support to the 31st Southern Africa Regional Climate Outlook Forum (SARCOF-31), held in Lusaka, Zambia, from 8–11 September 2025. The Alliance contributed to the forum through knowledge products, a technical presentation, and targeted capacity-building interactions that advanced the integration of climate forecasting into agricultural decision-making processes. Our support aligned with the SARCOF-31 theme “Closing the Early Warning Gap Together within the SADC Region” and sought to strengthen the interface between national meteorological services, agricultural institutions, and end-user communities. Key outcomes include the identification of climate-information needs for priority value chains, the design of pathways to enhance the flow of agro-climate advisories, and an assessment of decision-support tools for agricultural planning.